1998
DOI: 10.2307/3433631
|View full text |Cite
|
Sign up to set email alerts
|

Human Biomonitoring of Arsenic and Antimony in Case of an Elevated Geogenic Exposure

Abstract: Part of the norther Palat e region in Germany is erized by elevated leels of arsenic and antimony in the soil due to the presence ofore sources and former mining activities. In a biomonitoring study, 218 residents were investigted for a putative increased intake of these elements. Seventy-six nonexposd subjects in a rur region in south lower Saxony were chosen as the rrece group. Urine and scalp hair sampes were obtained as su to dein he miteral exposures to arsenic and antimony. The analys were pefr*m ed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 25 publications
(36 reference statements)
3
15
0
2
Order By: Relevance
“…Translocation of As from the soil to terrestrial plants made by root uptake or by absorption of airborne arsenic deposited on the leaves and certain species may accumulate high levels [1]. Nevertheless, even when these plants are grown in soil with high As content, the uptake is relatively low [35,36].…”
Section: Resultsmentioning
confidence: 99%
“…Translocation of As from the soil to terrestrial plants made by root uptake or by absorption of airborne arsenic deposited on the leaves and certain species may accumulate high levels [1]. Nevertheless, even when these plants are grown in soil with high As content, the uptake is relatively low [35,36].…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the extensive data for the toxicity of arsenic species, very little information concerning the toxicity of antimony species is available [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally assumed that arsenic and antimony have a similar geochemical behavior and a similar toxicity (Wilson et al 2004;Gebel et al 1998). Several years ago it was reported that only small amounts of Sb were found to be easily mobilizable from soils (Lintschinger et al 1998).…”
mentioning
confidence: 99%